2013
DOI: 10.1016/j.tube.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The changing face of tuberculosis: Trends in tuberculosis-associated skeletal changes

Abstract: Tuberculosis remains a major health problem in many areas of the world. Previous research suggested that the frequency of bone lesions has decreased in the modern (but pre-antibiotic) period, and that the predominantly spinal involvement have changed to affect other parts of the skeleton, in particular ribs. The purpose of this study was to investigate whether bone lesions associated with TB became more or less common in the post-antibiotic period, and if the pattern of skeletal involvement has changed. The sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 30 publications
(35 reference statements)
0
25
0
Order By: Relevance
“…In the study by Steyn et al (), it was found that about one third of all skeletons showed signs that could be associated with TB—this is much higher than the 2–4% that is generally reported in the literature (Vigorita, ; Holloway et al, ), but it should of course be kept in mind that these are people who have died from TB and do not represent the patient cohort at large. Skeletal involvement increased from the pre‐antibiotic period (around 21.1% of individuals), to 38.2% and 41.0% in the pre‐ and post‐1985 skeletons, respectively.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In the study by Steyn et al (), it was found that about one third of all skeletons showed signs that could be associated with TB—this is much higher than the 2–4% that is generally reported in the literature (Vigorita, ; Holloway et al, ), but it should of course be kept in mind that these are people who have died from TB and do not represent the patient cohort at large. Skeletal involvement increased from the pre‐antibiotic period (around 21.1% of individuals), to 38.2% and 41.0% in the pre‐ and post‐1985 skeletons, respectively.…”
Section: Introductionmentioning
confidence: 83%
“…The sample was divided into three groups based on their date of death—those who died before 1950 (1925–1949) and who probably did not receive any antibiotic treatment, those who died between 1950 and 1985 assumed to have been treated with antibiotics, and those who died after 1985 when co‐infection with HIV and drug‐resistant TB emerged. The date 1950 is used as post‐antibiotic as Streptomycin was introduced in the late 1940s and 1985 is used (somewhat arbitrarily) because the first cases of drug‐resistant TB and co‐infection with HIV in South Africa were reported around that time (Steyn et al, ). Unfortunately, all of the Western Cape skeletons dated from the antibiotic period.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence at York is higher at 3%. However, the crude prevalence rates presented here alongside the non-specific nature of many of the skeletal changes and the fact that majority of those with TB do not develop skeletal changes (Steyn et al 2013), means that the real rates of TB in medieval York are likely to have been higher.…”
Section: Airmentioning
confidence: 83%
“…According to authors, the high frequency of lesions supports the idea that antibiotics would lead to an extended course of disease, allowing more time for skeletal lesions to develop (Steyn et al. ). In the rib sample studied, the presence of similar lesions in individuals who lived and died before and after the introduction of antibiotics suggests that their immune system was strong enough to ensure relative survival, at least until the development of bone lesions.…”
Section: Discussionmentioning
confidence: 94%
“…Santos & Roberts, , ; Matos & Santos, ; Steyn et al. ; Mariotti et al. ; Steyn & Buskes, ), in which a possible causal relationship between periosteal rib lesions and pulmonary disorders, particularly tuberculosis, has been found.…”
Section: Introductionmentioning
confidence: 99%